2017
DOI: 10.1177/1534735416684946
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Licensed Acupuncturists in the San Francisco Bay Area: Prevalence of Treating Oncology Patients

Abstract: Background: Many cancer patients seek traditional Chinese medicine (TCM), the prevalence varying with diagnosis, comorbidities, and demographics. Interventions sought include acupuncture, massage, herbs, diet, and exercise, usually combined with conventional therapies. It is not known what proportion of TCM practitioners care for cancer patients, their cancer specific training or caseload, what interventions they employ, their outcomes, and their communication patterns with conventional oncologists. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Concerns about lack of training and experience treating oncology patients was identified as the second most reported barrier for conventional medicine providers in the SIO survey, scoring a 2.92 in a 4-point Likert scale. Based on the San Francisco Bay Area survey 5 there appears to be minimal oncology specific training among licensed acupuncturists with the majority reporting 100 hours or less. Ideally, licensed acupuncturist who treat people diagnosed with cancer would acquire oncology specific training as part of the standard curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerns about lack of training and experience treating oncology patients was identified as the second most reported barrier for conventional medicine providers in the SIO survey, scoring a 2.92 in a 4-point Likert scale. Based on the San Francisco Bay Area survey 5 there appears to be minimal oncology specific training among licensed acupuncturists with the majority reporting 100 hours or less. Ideally, licensed acupuncturist who treat people diagnosed with cancer would acquire oncology specific training as part of the standard curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four percent effective communication with oncologists and oncology care teams is especially important when treating people diagnosed with cancer. 5 One consideration is the change in blood counts that can come with conventional cancer treatments. 37 If the AHM practitioner is prescribing herbal formulas, as 79% of the respondents indicated in the San Francisco Bay Area survey, communication with the oncology care team is crucial due to potential herb-drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrative medicine is utilised by a substantial proportion of people with cancers [ 4 , 5 ] with acupuncture being used in both out-patient [ 6 ] and in-patient settings [ 7 , 8 ]. A review of acupuncture for symptom management in cancer found evidence of benefits [ 9 ] and an update found support for improvement in POI [ 10 ].…”
Section: Introductionmentioning
confidence: 99%